Hikayat Hang Tuah : petualangan pahlawan Nusantara yang diceritakan secara sastrawi nan heroik - Muhammad Haji Salleh (Jakarta : PT. Ufuk Publishing House, 2013)
Epic of Hang Tuah, a classical Malay literature.
In Indonesian, translated from Malay.
Koleksi sumbangan Tun (Dr.) Ahmad Sarji Abdul Hamid.
Keywords: Hikayat Hang Tuah; Malay literature, classical -- History and criticism